2015
DOI: 10.1590/0102-311x00090314
|View full text |Cite
|
Sign up to set email alerts
|

Agregação familiar e padrões alimentares na população brasileira

Abstract: The aim of the study was to identify dietary patterns in Brazil and verify aggregation among members of the same family based on the Brazilian National Dietary Survey, a nationwide dietary survey conducted in 2008-2009 in individuals over 10 years of age. Dietary intake was estimated with a food record. Dietary patterns were identified by factor analysis, and familial aggregation was verified by linear regression. Three major dietary patterns were identified: (1) a traditional snack featuring coffee, rolls, oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
16
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 58 publications
7
16
1
10
Order By: Relevance
“…However, such limitations are mitigated by detailing all deliberations [51]. It is noteworthy that the dietary patterns detected in this study were comparable with those of other studies, which validates the results obtained externally [27,30,34,[41][42][43].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, such limitations are mitigated by detailing all deliberations [51]. It is noteworthy that the dietary patterns detected in this study were comparable with those of other studies, which validates the results obtained externally [27,30,34,[41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…Determining food patterns in this population is an unprecedented finding, because of the method used to determine dietary patterns, highly recommended for approaching the actual behavior of the population studied [40,41], and for extrapolated the combination of nutrients and antinutritional factors involved in the human diet [40]. In addition, can meet the scarcity of studies that investigate the food consumption of farmers or rural populations and their associated factors [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], especially regarding their labor characteristics [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that although the fruit group did not appear in any dietary pattern in the present study, the frequency of fruit consumption was observed in all the other samples, with more than half of the elderly (58%) consuming three or more fruits daily 27 , and Figueira et al 28 stating that one of the factors that promotes fruit consumption is that such items are eaten in intervals between meals, and perhaps because of this are not associated with a particular eating occasion, together with other food items.…”
contrasting
confidence: 66%
“…esse pode ser observado não com os brasileiros transitando de uma alimentação tradicional para um padrão ultraprocessado, mas com contribuições dos ultraprocessados que sejam convenientes aos hábitos tradicionais e associados ao lazer e sociabilidade e ainda, pelo status social proporcionado, uma vez que indivíduos com menores estratos de renda ainda não têm acesso irrestrito a esse tipo de alimento. O declínio das refeições familiares parece não ser uma característica da sociedade brasileira, conforme indicou Massarani et al, (2015) mas o lazer parece estar associada ao consumo de ultraprocessados (BARBOSA, 2007;BARBOSA et al, 2018) e ainda, a alimentação diferenciada conforme a renda é uma característica importante da sociedade brasileira (SOUZA et al, 2013;BEZERRA et al, 2017;ANDRADE et al, 2018;SIMÕES et al, 2018a).…”
Section: Combinação Dos Eventos Alimentares Mais Frequentemente Consuunclassified